Data-driven decision analysis for weather observation technology in Japan: Integrating patent forecasting, network analytics, and economic valuation - Lee, Yong-Jae (Decision Making and Analysis, 2025)
Accurate weather observation is paramount for mitigating the severe impacts of natural disasters, particularly in geographically vulnerable countries like Japan. This study provides a data-driven analysis of recent patent trends in Japanese weather observation technology to identify high-potential areas for future investment. Given Japan’s susceptibility to extreme weather, enhancing forecast accuracy is crucial for economic and social resilience. We analyzed 93 patents published from 2019 to 2023 using an integrated methodology that combines patent mining, ARIMA-based time series forecasting, and Social Network Analysis (SNA). This approach enables us to identify key technologies, forecast their growth trajectories, and map their structural importance within the innovation ecosystem. Our analysis reveals that "control" technology is the leading field for future development, characterized by a rapidly growing ("Hot") trend and high structural centrality in the technology network. To validate its commercial relevance, we conducted an economic valuation using the Expected Value of Perfect Information (EVPI) and the Expected Value of Sample Information (EVSI). The results demonstrate a quantifiable positive return on investment for developing advanced control systems, confirming their economic viability. This research offers a robust, multi-faceted framework for strategic decision-making, providing actionable insights for stakeholders by directly linking technological forecasting to economic valuation.